Construction of a novel core-shell cermet/multiwall carbon nanotubes composite powder for thermal spraying. (October 2022) - Wei, Zheng; Wu, Yuping; Wei, Ziyu; Wang, Kailin; Zhu, Shuaishuai; Cheng, Jiangbo; Hong, Sheng
Abstract: Segregation, shedding and burnout of carbon nanotubes are the key issues limiting the development of carbon nanotube composite coatings for thermal spraying. In this work, multiwall carbon nanotubes (MWCNTs) were uniformly adsorbed on the cermet powder by surface modification method to form a porous and fluffy MWCNTs layer. Due to the high surface energy of MWCNTs layer, Ni–P particles were adsorbed on the surface of the composite powder and further grew to obtain a dense Ni–P plating, forming a unique core shell structure. Ni–P plating not only strengthened MWCNTs layer, but also effectively protected MWCNTs layer from burning during spraying. The superior thermal conductivity of graphitized MWCNTs layer and the excellent fluidity of Ni–P plating resulted in the full melting of composite powder surface, which effectively filled in the pores those generated in the deposition process. Through the strength of the graphitized MWCNTs, the nano hardness (H) and elasticity (E) of the composite coating increased by 17.73% and 33.63%, respectively. The porosity of the composite coating decreased by 31.20%. The preparation process of cermet/MWCNTs composite powder had application value in thermal spraying and powder metallurgy. Graphical abstract: Image 1 Highlights: Porous and fluffy MWCNTs layer was formed on WCN-PVA powder. MWCNTs layer were filled and coated by dense Ni–P alloy. Construct a composite powder with core-shell structures for spraying. Mechanical property of composite coating were improved by interlaminar MWCNTs.